Making Program Review Work for You - Carol Anne Costabile-Heming (Academic Chairpersons Conference Proceedings, 2015)
External program reviews result in unrealistic recommendations that emphasize increases in expenditures for operating budgets, human resources, and facilities, and viewed as a waste of time by faculty, chairs, and administrators. This session presents advantages of thoughtful, intentional review leading to concrete program improvement.
Keywords: program review; program assessment; continuous improvement; strategic planning